Evaluation of holistic education school through a quasi-experimental design: contributions from Physical Education - Pinilla Fonseca, Nicol; Gamboa Mora, María Cristina; Morales Barrera, Mónica (Retos, 2022)
The purpose of this study was to evaluate the holistic education achieved in high school students from the area of physical education based on the assessment of their perceptions, although it is true that currently there are numerous studies related to the subject, it is found that the way in which integral training should be developed is not addressed and when proposing the strategies, a horizon is drawn for its execution. A quasi-experimental design was used, in which a Likert scale instrument was applied with 57 items as diagnosis, statistically validated (Cronbach’s alpha 0.92) and by experts, later pedagogical-didactic strategies were implemented (traditional games, express what you think, recreation-swimming, gym practice and Munzee among others), aimed at integral development, finally the instrument was applied as a post-test and the significance of the differences was established with the Wilcoxon test. The sample was carried out with 180 students from San Isidro school from Espinal, which is a public school. The results of the dimensions showed significant statistical changes from the students’ point of view, the positive ranges are indicators regarding a better perception of the holistic education taught in PE (physical education). In conclusion, the implementation of didactic and pedagogical strategies of PE contribute to the students’ holistic education, ethical and socioemotional realm, which represent a substantial contribution.